Ophthalmic surgeries at a Nigerian teaching hospital from the perspectives of undergraduate medical education - Abdulraheem Olarongbe Mahmoud; Abdulkabir Ayansiji Ayanniyi; Yinka Ologunsua; Susannah Adepoju (Clinical Epidemiology and Global Health)
Background: An appraisal of the profile of ophthalmic surgeries performed at Ladoke Akintola University of Technology Teaching Hospital (LAUTECHTH), Ogbomosho, Nigeria over a seven-year period with a view to harnessing their potentials for maximising ophthalmic experiences of medical students. Methods: A retrospective review of ophthalmic surgery records over a seven-year period (2013–2019) at LAUTECHTH. Results: There were 386 eye surgeries, mean ophthalmic surgeries: 4–5/month or 55/year. Most (329, 85.2 %) surgeries were performed on individuals aged at least 45 (range 10–95) years with slight male dominance (1.1:1). The most common indication for surgery was cataract (307, 79.6 %). Most surgeries were elective (362, 93.8 %) and performed under local anaesthesia (367, 95.1 %). Despite the highest number of surgeries being performed in the months of April and September; and lowest during the months of May and October; there was fair distribution across and over the years. Small incision cataract surgery with or without intraocular lens implant (307, 79.6 %) was the most common surgery followed by pterygium excision with adjuvant therapy (37, 9.6 %). Conclusion: The study showed a broad spectrum of eye surgeries, including cataract and pterygium, performed at the teaching hospital, encompassing common conditions that lead to visual impairment or blindness. This exposure provides valuable training opportunities for undergraduate medical students to become physicians especially those aspiring to become ophthalmologists. However, there is a need to increase the overall volume of eye surgeries to enhance the learning experience and potentially influence career choices.